2017
DOI: 10.1534/g3.117.041053
|View full text |Cite
|
Sign up to set email alerts
|

NuA4 Lysine Acetyltransferase Complex Contributes to Phospholipid Homeostasis inSaccharomyces cerevisiae

Abstract: Actively proliferating cells constantly monitor and readjust their metabolic pathways to ensure the replenishment of phospholipids necessary for membrane biogenesis and intracellular trafficking. In Saccharomyces cerevisiae, multiple studies have suggested that the lysine acetyltransferase complex NuA4 plays a role in phospholipid homeostasis. For one, NuA4 mutants induce the expression of the inositol-3-phosphate synthase gene, INO1, which leads to excessive accumulation of inositol, a key metabolite used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Though non-essential, the EAF1 subunit is a critical scaffolding protein required to maintain the complete NuA4 complex [ 16 , 19 ]. Yeast cells deficient for Eaf1 are viable but lose much of the targeting of the catalytic Esa1 subunit, making the eaf1Δ mutant an excellent genetic model system to identify the biological roles and protein targets of NuA4 [ 16 , 18 , 20 , 21 ]. Alternatively, NuA4 function can be probed using the temperature sensitive mutation, esa1-ts ( esa1-L245P ), which reduces the acetylation activity of Esa1 at increased temperatures [ 2 , 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though non-essential, the EAF1 subunit is a critical scaffolding protein required to maintain the complete NuA4 complex [ 16 , 19 ]. Yeast cells deficient for Eaf1 are viable but lose much of the targeting of the catalytic Esa1 subunit, making the eaf1Δ mutant an excellent genetic model system to identify the biological roles and protein targets of NuA4 [ 16 , 18 , 20 , 21 ]. Alternatively, NuA4 function can be probed using the temperature sensitive mutation, esa1-ts ( esa1-L245P ), which reduces the acetylation activity of Esa1 at increased temperatures [ 2 , 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further experimental validation will reveal the molecular mechanism underlying the recruitment of the NuA4 complex. In support of this, recent studies ( 20 , 21 ) demonstrated the new mechanistic dissection between the NuA4 complex and phospholipid homeostasis, further enforcing the suggested direct link between ESA1 and OPI1.…”
Section: Resultsmentioning
confidence: 56%
“…De-repressing translation of ACC1 and FAS1 corrects mitotic phenotypes of sec14 mutants Conditional sec14 mutants proliferate at 25°C, but not at 37°C (Novick et al, 1980) . Furthermore, inhibition of lipogenesis by cerulenin exacerbates the temperature sensitivity of sec14-1 cells (Dacquay et al, 2017) . Whereas the cerulenin effect is a rather non-specific phenotype (Lee et al, 2014) , this observation raised the question of whether the increased lipogenesis in uORFm-ACC1,FAS1 cells could suppress the temperature-sensitive proliferation of sec14-1 cells.…”
Section: Lipogenesis Controls the Timing Of Nuclear Divisionmentioning
confidence: 99%